Evaluation of 22 Primary Gastrointestinal Lymphoma Patients - ŞİMŞEK, MELİH; Yildirim, Nilgun; Turkeli, Mehmet; Akdemir, Mehmet Naci; Simsek, MELİH; TEKİN, Salim Başol (My University, 2019)
Objective: Primary gastrointestinal non-hodgkin lymphomas (PGI-NHL) are uncommon diseases with treatment modalities including chemotherapy, surgery, and radiotherapy. Our aim is to analyze the demographic and clinical features and treatment results of PGI-NHL.